Review Article: Worldwide Measles Outbreak Post-2020 - Ibrahim, Maryam Sabri; Ali Fatal, Ghassan; Hadi Sakeh, Tahreer (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Even though it is thought to be eliminated in the world, measles (Rubeola) still sometimes comes out. Refusing vaccination creates susceptible groups of people who might get the virus if it is brought into the country from an endemic area. These people might then infect newborns as well as susceptible people with the virus. The illness and the elements which increase a possibility of transmission were unfamiliar for numerous healthcare professionals. This dangerous infectious disease called measles could lead to vision loss, deafening a respiratory infection, neurological problems, as well as mortality. Oral vitamin A therapy with supporting treatment is necessary for rubella sufferers. Although the rubella vaccine is quite harmless or secure, certain parts of the nation have seen a decline in vaccination rates due to inaccurate data about the efficacy of this or similar vaccines. Each state has obligatory vaccination regulations under place, or these regulations have been maintained by courts, particularly the US Supreme Court. However, each state has its own set of exclusions as well as rules. In the treatment of rubella patients, case authentication, or dissemination prevention, nursing may be quite helpful. Above all, nurses ought to be dedicated front-line champions of vaccination as women occupy situations of confidence throughout our societies. This article's goal is to enlighten readers on measles, including its signs and symptoms, indicators, prevention, treatment options, as well as relevant regulations and legislation.